Photovoltaic Power System with MPPT Functionality for a Small-Size Electric Vehicle - Jianming Xu; Longyun Kang; Changyi Zhong; Binggang Cao (International Journal of Photoenergy)
Electric vehicles are recognized as the best replacement of petrol vehicles in the future. However, there are several problems hampering their development, such as the short life span of batteries, poor performance of start-up, and a short driving range. In order to resolve these problems, a hybrid power system based on photovoltaic (PV) cells, supercapacitors, and batteries is proposed. This paper focuses on PV cells using a maximum power point track (MPPT) system based on a BUCK chopper circuit. Moreover, a novel MPPT algorithm named sectional variable step climbing (SVSC) algorithm was proposed. To validate the proposed system, two main experiments have been done. The first experiment showed that the MPP of PV cells was tracked perfectly by use of this photovoltaic power system. The second one showed that the efficiency of SVSC was higher than two existing MPPT methods, the climbing algorithm and the open-circuit voltage (OCV) algorithm.